2016
DOI: 10.3389/fnagi.2015.00249
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and Cognitive Reserve: A Critical Overview and a Plea for Methodological Innovations

Abstract: The decline of cognitive skills throughout healthy or pathological aging can be slowed down by experiences which foster cognitive reserve (CR). Recently, some studies on Alzheimer's disease have suggested that CR may be enhanced by life-long bilingualism. However, the evidence is inconsistent and largely based on retrospective approaches featuring several methodological weaknesses. Some studies demonstrated at least 4 years of delay in dementia symptoms, while others did not find such an effect. Moreover, vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 178 publications
(285 reference statements)
3
70
4
2
Order By: Relevance
“…So far, research on CR in bilinguals with AD has largely neglected this factor, as most samples included participants who spoke widely diverse language pairs. In the studies by Bialystok and colleagues, for instance, bilingual participants spoke any of several native languages (e.g., German, Yiddish, Polish, Farsi, and French)-for a review, see Calvo et al, (2015). In particular, some of the studies reporting null results have assessed only distant language pairs (Crane et al, 2010;Kousaie and Phillips, 2012;Zahodne et al, 2014).…”
Section: Reservations Concerning the Hypothesis' Cross-linguistic Genmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, research on CR in bilinguals with AD has largely neglected this factor, as most samples included participants who spoke widely diverse language pairs. In the studies by Bialystok and colleagues, for instance, bilingual participants spoke any of several native languages (e.g., German, Yiddish, Polish, Farsi, and French)-for a review, see Calvo et al, (2015). In particular, some of the studies reporting null results have assessed only distant language pairs (Crane et al, 2010;Kousaie and Phillips, 2012;Zahodne et al, 2014).…”
Section: Reservations Concerning the Hypothesis' Cross-linguistic Genmentioning
confidence: 99%
“…On the other hand, insights from the embodied cognition framework point to deficits in syntax and action-verb processing as early (and even preclinical) markers of PD (García and Ibáñez, 2014;Garcia et al, 2016;. Both lines of research have attracted increasing attention in recent years, leading to novel theoretical Calvo et al, 2015;Cardona et al, 2013;Bak, 2013) and clinical (Bialystok et al, 2007;Alladi et al, 2015;García & Ibáñez, 2014;Melloni et al, 2015) formulations of potential relevance for public health (Bialystok et al, 2016;García et al, 2017;Bocanegra et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, inconsistent results have been reported in other studies [5-7], which demonstrated that the age of dementia diagnosis was not significantly different between bilinguals and monolinguals. The potential reasons for the contradictory findings suggested by Calvo et al [8] were methodological differences in the definition of bilingualism, the sample design, the definition of age of onset, and the consideration of other variables known to affect CR. Moreover, diverse language pairs used by the bilinguals in different studies may also contribute to the discrepancies.…”
Section: Introductionmentioning
confidence: 98%
“…This perspective, however, remains controversial and sometimes no bilingual advantage on cognition is reported (e.g., Dick et al, 2019). Calvo, García, Manoiloff & Ibáñez (2016) in a review paper found that only that around 60-70% of published data have found a cognitive reserve effect of bilingualism on cognitive decline. Recently Lehtonen et al (2018) compared the bilinguals' and monolinguals' performance in six executive domains based on 152 studies on adults.…”
Section: Introductionmentioning
confidence: 99%